ANALISIS KONFLIK SOSIAL DALAM CERPEN SERTIFIKAT KARYA ENDANG S SULISTIYA: KAJIAN SOSIOLOGI SASTRA - Lestari, Elsa Zakia; Setyorini, Ririn (DIALEKTIKA JURNAL PENDIDIKAN BAHASA INDONESIA, 2024)
This study aims to analyze, explain, and describe social conflict in the short story "Sertifikat" (Certificate) by Endang S Sulistiya using a literary sociology approach. This research is a qualitative study that is descriptive in nature. Data collection is onducted through literature review using the technique of reading and note-taking. The data for this research consists of quotations from character dialogues in the short story "Sertifikat" by Endang S Sulistiya. The data collection technique uses document content analysis. The data analysis technique uses he Miles and Huberman model, which includes data collection, data reduction, data display, and drawing conclusions or verification. The findings of the research indicate that the short story "Sertifikat" by Endang S Sulistiya contains social conflicts, including: 1) Latent conflicts, which involve issues of injustice in land ownership rules, regulatory changes, and the obligation to comply with the law as underlying elements, 2) Open conflicts, which present a clear depiction of conflict escalation, threats faced, and actions taken to confront the conflict, 3) Surface conflicts, which involve misunderstandings and lack of understanding in character communication that can potentially develop into further conflict. Keywords: social conflict, short story, sociology.